2003
DOI: 10.1083/jcb.200304069
|View full text |Cite
|
Sign up to set email alerts
|

Differential requirements for AP-2 in clathrin-mediated endocytosis

Abstract: AP-2 complexes are key components in clathrin-mediated endocytosis (CME). They trigger clathrin assembly, interact directly with cargo molecules, and recruit a number of endocytic accessory factors. Adaptor-associated kinase (AAK1), an AP-2 binding partner, modulates AP-2 function by phosphorylating its μ2 subunit. Here, we examined the effects of adenoviral-mediated overexpression of WT AAK1, kinase-dead, and truncation mutants in HeLa cells, and show that AAK1 also regulates AP-2 function in vivo. WT AAK1 ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
152
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(170 citation statements)
references
References 30 publications
14
152
1
3
Order By: Relevance
“…Consistently, AP-2 was found not to be required for direct interaction with the EGFR for clathrin-dependent internalization of the EGFR (Huang et al, 1999;Nesterov et al, 1999). Furthermore, it was recently reported that the EGFR was efficiently endocytosed even in the absence of AP-2 upon RNA interference knock-down (Conner and Schmid, 2003;Motley et al, 2003). This could be consistent with the possibility that ubiquinated EGFR interacts directly with an endocytosis adaptor harboring a ubiquitin-interacting domain.…”
Section: Discussionsupporting
confidence: 72%
“…Consistently, AP-2 was found not to be required for direct interaction with the EGFR for clathrin-dependent internalization of the EGFR (Huang et al, 1999;Nesterov et al, 1999). Furthermore, it was recently reported that the EGFR was efficiently endocytosed even in the absence of AP-2 upon RNA interference knock-down (Conner and Schmid, 2003;Motley et al, 2003). This could be consistent with the possibility that ubiquinated EGFR interacts directly with an endocytosis adaptor harboring a ubiquitin-interacting domain.…”
Section: Discussionsupporting
confidence: 72%
“…We have recently shown that these adaptors can function even in the absence of any detectable AP-2. When we knock down AP-2 in HeLa cells using siRNAs, clathrin-mediated endocytosis of the transferrin receptor goes down to background levels, but clathrin-mediated endocytosis of the EGF receptor and of an LDL receptor chimera (as assayed by binding the ligand to the cell surface at 4°C and then warming the cells to 37°C) still proceed normally, even though there are 12-fold fewer clathrin-coated pits at the plasma membrane see also Conner and Schmid, 2003;Hinrichsen et al, 2003;Huang et al, 2004). Thus, it now appears that AP-2 is just one, albeit very abundant, adaptor for clathrin-mediated endocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing evidence has shown that not all cargo molecules are internalized through an interaction with AP-2 (3,4). Both LDL and EGF are among the known examples of AP-2-independent cargos involved in clathrin-mediated endocytosis (5,6). Various cargo-specific adaptor proteins have been proposed to function as alternative adaptors for clathrinmediated endocytosis, but the exact adaptor proteins used by most of the AP-2-independent cargos are still unknown (3,4).…”
mentioning
confidence: 99%